Monstress. Volume 7, Devourer - Liu, Marjorie M.; Takeda, Sana (Image Comics, 2022)
Humans and Arcanics are at war once again, but battles of the heart and soul are the most dangerous of all. Caught in the calculating grip of the Dusk Court, Maika and Zinn uncover painful secrets of the past while Tuya fights to preserve her future - and young Kippa might be the Known World's only hope for the present.
Keywords: Halfwolf, Maika : (fiktiivinen hahmo); yliluonnolliset voimat; tytöt; teini-ikäiset; hirviöt; vaihtoehtoiset todellisuudet